Psychological Well-being pada Guru Honorer di Indonesia : A Literature Review - Lalu Reza Gunawan; Wiwin Hendriani (Psikoislamedia : Jurnal Psikologi, 2019)
Teachers are one of the most important parts of education because they play a direct role in shaping the quality of learning, in Indonesia the teachers themselves consist of PNS teachers and teachers who are not employees or are called honorary teachers. Honorary teacher's life is relatively far from prosperous because the salary received is far below the salary of teachers who are civil servants. Fulfillment of psychological needs in individuals associated with psychological well-being owned, where the more fulfilled the psychological needs of the person, the psychological well-being will also increase. This research is interesting because in the literature used there is a result that Well-being found in honorary teachers gets high and medium scores, the influence of stress in work situations and gratitude also affects well-being in honorary teachers in Indonesia.